Training volume and altitude training are associated with power output and race results: A longitudinal case study of an elite female cyclist - Mennen, B.; Hesselink, M. K. C.; Delahaye, L.; van Hooren, B. (Journal of Science and Cycling, 2024)
Introduction Since the introduction of the UCI Ladies World Tour in 2016, the popularity of female competitive cycling has grown exceptionally. While training characteristics that correlate with power-output and racing results have been fairly well established in male elite cyclists, only little research has investigated these characteristics in female cyclists. However, the distinct nature of racing, with higher intensities and shorter distance covered in females compared to males, the physiological sex differences and the brief history of female cycling urge for sex specific examination of determinants of bike racing performance. Further, previous research investigated professional but not world-class level female cyclists. Thus, the aim of this study was to identify training characteristics that are related to power output and race results in a world-class female cyclist. Moreover, this analysis permitted the identification of key characteristics including length, duration and power outputs of classical races and grand tours where this cyclist excelled.